2023
DOI: 10.1038/s41598-023-34559-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of machine learning to assess the prognostic utility of radiomic features for in-hospital COVID-19 mortality

Abstract: As portable chest X-rays are an efficient means of triaging emergent cases, their use has raised the question as to whether imaging carries additional prognostic utility for survival among patients with COVID-19. This study assessed the importance of known risk factors on in-hospital mortality and investigated the predictive utility of radiomic texture features using various machine learning approaches. We detected incremental improvements in survival prognostication utilizing texture features derived from eme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Most of the COVID-19 prognostic models reported in the literature, especially for hospitalized patients, base their predictions on demographics (with age and sex as the most determinant variables), comorbidities (with special focus on hypertension, cardiovascular disease, hypertension and diabetes), laboratory indicators (e.g., lymphocyte/platelet counts, creatinine, interleukin 6 (IL-6), procalcitonin (PCT), d-dimer, ferritin etc.) (139,140) and medical imaging (141). In a recent systematic and extensive review about the various COVID-19 prognostic models presented in the literature, the divergence between the reported performance statistics is highlighted (142).…”
Section: Scov2 Diagnostic and Prognostic Modelling: A Machine Learnin...mentioning
confidence: 99%
“…Most of the COVID-19 prognostic models reported in the literature, especially for hospitalized patients, base their predictions on demographics (with age and sex as the most determinant variables), comorbidities (with special focus on hypertension, cardiovascular disease, hypertension and diabetes), laboratory indicators (e.g., lymphocyte/platelet counts, creatinine, interleukin 6 (IL-6), procalcitonin (PCT), d-dimer, ferritin etc.) (139,140) and medical imaging (141). In a recent systematic and extensive review about the various COVID-19 prognostic models presented in the literature, the divergence between the reported performance statistics is highlighted (142).…”
Section: Scov2 Diagnostic and Prognostic Modelling: A Machine Learnin...mentioning
confidence: 99%
“…Using various machine learning approaches, the prognostic value for survival of COVID-19 patients based on known in-hospital mortality risk factors and chest radiographs was assessed. It was found that the indicators should include age, oxygen saturation, blood pressure, and some concomitant diseases, as well as image features related to the intensity and variability of the pixel distribution [126].…”
mentioning
confidence: 99%